2018
DOI: 10.1021/acs.langmuir.8b00947
|View full text |Cite
|
Sign up to set email alerts
|

Reversible “Off–On” Fluorescence of Zn2+-Passivated Carbon Dots: Mechanism and Potential for the Detection of EDTA and Zn2+

Abstract: Zn-passivated carbon dots (named Z-CDs) were synthesized from zinc gluconate for the first time through a one-step pyrolysis treatment. The mechanism of Zn-enhanced fluorescence was carefully investigated, and a new strategy to passivate the surfaces of CDs by Zn was proposed. Inspired by the complexation reaction between Zn and ethylenediaminetetraacetic acid (EDTA), a reversible "off-on" fluorescent nanosensor for the detection of EDTA and Zn was constructed based on the depassivation and repassivation of Z-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 82 publications
(41 citation statements)
references
References 47 publications
1
40
0
Order By: Relevance
“…More importantly, CPDs show the narrowest FWHM of 20 nm, which is far superior to previously reported CDs, commercial organic dyes with deep red fluorescence, and even equal to the best Cd 2+ /Pb 2+ ‐based QDs (FWHM < 30 nm). [ 8,9,28,32,34 38 ] In vivo imaging demonstrates that CPDs can serve as outstanding deep red fluorescent probe with excellent biocompatibility and fast clearance with minimal retention postimaging. They are also potentially applied to the fields of drug delivery, photothermal therapy, and photoelectron conversion owing to their deep red excitation and emission, high QY, broad absorption, and extremely narrow FWHM.…”
Section: Figurementioning
confidence: 99%
“…More importantly, CPDs show the narrowest FWHM of 20 nm, which is far superior to previously reported CDs, commercial organic dyes with deep red fluorescence, and even equal to the best Cd 2+ /Pb 2+ ‐based QDs (FWHM < 30 nm). [ 8,9,28,32,34 38 ] In vivo imaging demonstrates that CPDs can serve as outstanding deep red fluorescent probe with excellent biocompatibility and fast clearance with minimal retention postimaging. They are also potentially applied to the fields of drug delivery, photothermal therapy, and photoelectron conversion owing to their deep red excitation and emission, high QY, broad absorption, and extremely narrow FWHM.…”
Section: Figurementioning
confidence: 99%
“…of the CPDs by changing the chemical and electronic structure. The common doping elements include nitrogen,79c,86 phosphorus, sulfur, boron,87d,89 and some metals,26c,90 etc. Some recently reported doped CPDs are shown in Table 1 with the synthesis methods and some properties of CPDs.…”
Section: Synthesis Of Cpds By Bottom‐up Methodsmentioning
confidence: 99%
“…raw materials. In addition to the nonmetallic element doping, the metal element doping was also frequently used to regulate CPDs' property and confer CPDs' function 26c,90,91b,92. Chen et al synthesized Gd‐doping CPDs from Gd(NO 3 ) 3 and m‐phenylenediamine by ethanol solvothermal (Figure c).…”
Section: Synthesis Of Cpds By Bottom‐up Methodsmentioning
confidence: 99%
“…All the optical and structure characterizations suggested that the new kind of Mg 2+ -doped CDs had been successfully synthesized in the present work, we considered during the process of hydrothermal reaction, the carbohydrate portion was carbonized to form CDs core, simultaneously the Mg 2+ were in situ doped into CDs, interacted with the carboxylate functional groups on the surfaces. [27] Before exploring the application of Mg-CDs in inducing osteoblastic differentiation, the cytotoxicity and cellular uptake of Mg-CDs was tested for MC3T3-E1 cell lines. It could be seen that when the culture dose of Mg-CDs was as high as 800 µg mL −1 , the cell viability could still retain around 80% ( Figure S2a, Supporting Information), demonstrating the low toxicity and excellent biocompatibility of Mg-CDs.…”
Section: Osteogenic Biomaterialsmentioning
confidence: 99%
“…As we expected, the color of Mg‐CDs solution changed from purple red to bluish violet after adding Magneson I, while the color of CDs without Mg 2+ dopants remained unchanged (Figure S1, Supporting Information). All the optical and structure characterizations suggested that the new kind of Mg 2+ ‐doped CDs had been successfully synthesized in the present work, we considered during the process of hydrothermal reaction, the carbohydrate portion was carbonized to form CDs core, simultaneously the Mg 2+ were in situ doped into CDs, interacted with the carboxylate functional groups on the surfaces …”
mentioning
confidence: 94%